Aquatic Pollution and Risks to Biodiversity: The Example of Cocaine Effects on the Ovaries of Anguilla anguilla - Mayana Karoline Fontes; Luigi Rosati; Mariana Di Lorenzo; Camilo Dias Seabra Pereira; Luciane Alves Maranho; Vincenza Laforgia; Anna Capaldo (Animals, 2022)
Pollution is one of the main causes of the loss of biodiversity, currently one of the most important environmental problems. Important sources of aquatic pollution are illicit drugs, whose presence in waters is closely related to human consumption; their psychoactive properties and biological activity suggest potential adverse effects on non-target organisms, such as aquatic biota. In this study, we evaluated the effect of an environmentally relevant concentration of cocaine (20 ng L-1), an illicit drug widely found in surface waters, on the ovaries of Anguilla anguilla, a species critically endangered and able to accumulate cocaine in its tissues following chronic exposure. The following parameters were evaluated: (1) the morphology of the ovaries; (2) the presence and distribution of enzymes involved in oogenesis; (3) serum cortisol, FSH, and LH levels. The eels exposed to cocaine showed a smaller follicular area and a higher percentage of connective tissue than controls (p < 0.05), as well as many previtellogenic oocytes compared with controls having numerous fully vitellogenic and early vitellogenic oocytes. In addition, the presence and location of 3β-hydroxysteroid dehydrogenase, 17β-hydroxysteroid dehydrogenase, and P450 aromatase differed in the two groups. Finally, cocaine exposure decreased FSH and LH levels, while it increased cortisol levels. These findings show that even a low environmental concentration of cocaine affects the ovarian morphology and activity of A. anguilla, suggesting a potential impact on reproduction in this species.